Cuidados em saúde bucal de crianças com Transtorno do Espectro Autista acompanhadas em um centro especializado em reabilitação - Fontenele, Geórgia Yngrid Gomes (2025)
Autism Spectrum Disorder involves neurodevelopmental impairments, and some conditions associated with autism, such as sensory alterations, may have a negative impact on oral health. Given the scarcity of evidence in the literature, the following guiding questions were developed to conduct this study: How is oral health care carried out by parents/caregivers of children with autism? How these caregivers deal with and overcome possible challenges in performing such care? In this regard, the objective of this study is to understand the oral health care practices developed by parents/caregivers of young children with Autism Spectrum Disorder. This is a descriptive-exploratory case study with a qualitative approach. The study was conducted in the Autism Spectrum Disorder unit of the Early Treatment and Stimulation Center in Fortaleza, Ceará. The eligible sample included parental and non-parental caregivers aged 18 years or older, who were responsible for children aged 3 to 5 years with a clinical diagnosis of autism receiving care at the center. Data collection took place between July and September 2024 after approval of the research project to the Research Ethics Committee of the Federal University of Ceará. The study consisted of semi-structured interviews guided by key questions. Data collection ended after seven interviews, upon reaching theoretical saturation. The interviews were recorded and subsequently transcribed. For analysis, Thematic Content Analysis developed by Laurence Bardin was used. The coding process was carried out with the aid of the Atlas.ti software. From the thematic analysis, 26 codes emerged from 263 recording units, distributed across three main categories: “Oral health care for children with ASD,” “Challenges in oral health care for children with ASD,” and “Strategies for oral health care for children with ASD.” Based on the reports, it is evident that most mothers do not have adequate support for daily oral care routines and have not received oral health guidance from dentists. It is hoped that this study will contribute to future research and foster the development of public policies regarding the oral health of children with autism.